2004
DOI: 10.1093/ndt/gfh307
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence in Switzerland of pure red-cell aplasia due to anti-erythropoietin antibodies in chronic dialysis patients: report of five cases

Abstract: Background. Pure red-cell aplasia (PRCA) after erythropoietin (Epo) administration due to the appearance of neutralizing anti-Epo antibodies has been reported in over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Previous studies of PRCA in CHC patients have largely been single case reports pointing to the rarity of the disease [2][3][4][5][6][7][8][9], and studies in populations of dialysis patients have indicated that the prevalence of PRCA could be as low as one case per 10,000 or 100,000 patients [10,12], which is consistent with the upper bound of the 95% CI for the PRCA incidence estimates we report. One hospital-based survey in France identified 2 PRCA cases among 6,630 CHC patients, however both cases were receiving EPO therapy which has been linked to PRCA development through the formation of anti-erythropoietin antibodies [6,7].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies of PRCA in CHC patients have largely been single case reports pointing to the rarity of the disease [2][3][4][5][6][7][8][9], and studies in populations of dialysis patients have indicated that the prevalence of PRCA could be as low as one case per 10,000 or 100,000 patients [10,12], which is consistent with the upper bound of the 95% CI for the PRCA incidence estimates we report. One hospital-based survey in France identified 2 PRCA cases among 6,630 CHC patients, however both cases were receiving EPO therapy which has been linked to PRCA development through the formation of anti-erythropoietin antibodies [6,7].…”
Section: Discussionsupporting
confidence: 89%
“…One hospital-based survey in France identified 2 PRCA cases among 6,630 CHC patients, however both cases were receiving EPO therapy which has been linked to PRCA development through the formation of anti-erythropoietin antibodies [6,7]. The formulation of EPO varies by country, and different formulations may confer different PRCA risks leading to variations in PRCA prevalence by country among EPO treated patients [12]. It is possible, therefore, that there were no PRCA cases in our cohort of more than 36,000 CHC patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Overall, Switzerland had the highest PRCA prevalence with 1 case per 460 epoetin-treated chronic kidney disease patients. 34 Spain had the lowest hematologic recovery rates and the highest rates of intravenous immunoglobulin use as immunosuppressive therapy, whereas all 6 of the Singapore PRCA patients recovered, 5 of whom had received cyclosporine for immunosuppression. A published case series from Thailand described 4 epoetin-associated PRCA patients who failed to recover epoetin responsiveness after immunosuppressive therapy initially but recovered epoetin responsiveness shortly after undergoing renal transplantation.…”
Section: Pure Red Cell Aplasia Antibodies and Epoetin 3345 Blood 1mentioning
confidence: 96%
“…The RADAR group reported similar exposure‐adjusted incidence rates per 10,000 chronic kidney disease patients: 0.2 for Epogen/Procrit, 0.2 for epoetin beta, and 4.5 and 2.0 for Eprex without HSA in 2002 and 2003, respectively; the exposure‐adjusted incidence rate per 10,000 patient‐years for Eprex‐associated PRCA peaked at 4.5 in 2002 and decreased to 2.0 in 2003. Swiss Medic reported that before 2004, a total of 2300 Swiss chronic kidney disease patients had received epoetin alfa or epoetin beta and 5 patients had developed antibody‐associated PRCA—resulting in an estimated PRCA incidence with epoetin beta of 0.14 per 10,000 patient‐years versus 1.4 per 10,000 patient‐years with Eprex 19 …”
Section: Resultsmentioning
confidence: 99%